(untitled) (Global Journal of Science Frontier Research, 2015)
A study was conducted in Thovalai and Vilavancode Taluks in Kanyakumari District of Tamil Nadu to evaluate the Status of drinking water from shallow wells and bore-holes with respect to different physic-chemical parameter Temperature, pH, turbidity, alkalinity, hardness, salinity, fluoride, chloride total dissolved solids, dissolved oxygen, BOD, electrical conductivity total nitrogen, nitrate, sulphate ,ammonia, phosphate, total phosphorus, sodium, potassium and oxidation and reduction potential water samples were collected from different places from the taluks. Results reveal that almost all the Physic-Chemical parameter including the elemental investigations of the shallow wells and bore-holes have values within the range of permissible levels for drinking water. It was found that most of the parameters are within the permissible levels as described by WHO (1984).